THE WISDOM OF CREATING HUMOR IN THAI PARODY - CONTEMPORARY POETRY - Klinchandaeng , Tanamon (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2020)
This article aims to study the wisdom of creating a sense of humor in the contemporary Thai verse literature. The objective of this study is to study strategies for linking with the underlying literature and strategies for creating comedy by analyzing two contemporary poems namely “I therefore came to find the sorrow ” of Phaibun Wongthet and “Parasavatthi” from Komthuan Bowen. The study result showed that Thai contemporary verse literature uses 3 methods of linking with original literature: 1) Mimicking words; 2) Mimicking sounds; and 3) Mimicking poetry. Considering the ways to create humor, the 6 ways were found namely: 1) Creating content contrary to the original literature; 2) Creating content or ideas against one another; 3) Using language contrary to literary symbolism; 4) Contrasting; 5) Playing with the meaning of words and 6) Using words that represent sex. The study of parody literature in the genre of Thai contemporary poetry reflected the author’s wisdom in language usage and poetry as well as showing the wisdom of society that uses parody literature as a means of expressing feelings and the humor of the Thai people.